Implementasi dan Upaya Mengatasi Problematika Pembelajaran PAI di SD Tanah Bara, Aceh - Manik, Rajikin (Abdurrauf Social Science, 2024)
This study is to examine the learning problems of Islamic religious education in SD Tanah Bara, Gunung Meriah District, Aceh Singkil Regency, The formulation of the problem in this study is: 1) How is the implementation of PAI learning in SD Tanah Bara? 2) What are the problems in learning Islamic Religious Education (PAI) at SD Tanah Bara? 3) What are the efforts made to overcome the learning problems of Islamic Religious Education (PAI) in SD Tanah Bara?. This study uses a qualitative approach that is intended to know and describe clearly and in detail the problems of learning Islamic religious education in SD Negeri Tanah Bara, Gunung Meriah District, Aceh Singkil Regency. The data collection technique used is a questionnaire. The results of the research are the implementation of Islamic religious education learning at SD Negeri Tanah Bara, however, only 2 hours a week, there are several factors that are problems in learning Islamic religious education at SD Negeri Tanah Bara, including the lack of Islamic Religious Education teachers, lack of facilities/facilities at school, and lack of support from parents and lack of interest from students. The effort to overcome these problems is by increasing PAI lesson hours, providing motivation, providing the right methods and preferred by students and completing books related to Islamic religious education learning. [Abstrak: Penelitian ini adalah untuk mengkaji problematika pembelajaran pendidikan agama Islam di SD Tanah Bara Kec. Gunung Meriah Kab. Aceh Singkil, Rumusan masalah dalam penelitian ini adalah: 1) Bagaimana pelaksanaan pembelajaran PAI di SD Tanah Bara? 2) Apa saja yang menjadi problematika dalam pembelajaran Pendidikan Agama Islam (PAI) di SD Tanah Bara? 3) Apa saja upaya yang dilakukan untuk mengatasi problematika pembelajaran Pendidikan Agama Islam (PAI) di SD Tanah Bara?. Penelitian ini menggunakan pendekatan kualitatif yang dimaksudkan untuk mengetahui dan mendeskripsikan secara jelas dan rinci tentang problematika pembelajaran pendidikan agama Islam di SD Negeri Tanah Bara Kecamatan Gunung Meriah Kabupaten Aceh Singkil. Adapun tehnik pengumpulan data yang digunakan yaitu angket. Adapun hasil penelitiannya adalah adanya pelaksanaan pembelajaran pendidikan agama Islam di SD Negeri Tanah Bara namun, hanya 2 jam dalam seminggu, ada beberapa faktor yang merupakan problem pembelajaran pendidikan agama Islam di SD Negeri Tanah Bara diantaranya sedikitnya guru Pendidikan Agama Islam, kurangnya sarana/fasilitas di sekolah, dan kurangnya dukungan dari orang tua serta kurang minat dari peserta didik. Adapun upaya untuk mengatasi problematika tersebut dengan cara menambah jam pelajaran PAI, memberi motivasi, memberikan metode yang tepat dan disukai oleh anak didik serta melengkapi buku-buku terkait pembelajaran pendidikan agama Islam.